Literature and film as modern mythology - Ferrell, William K., 1930- (Praeger, 2000)
Novels and films record and codify the cultural experiences of people. This book explores the relationship between contemporary literature and film over the past 50 years and the ancient myths of Judeo-Christian, Greek, Celtic, and Eastern origin.